Sedimentary responses to the Indian Summer Monsoon variations recorded in the southeastern Andaman Sea slope since 26 ka. (15th December 2015) - Cao, Peng; Shi, Xuefa; Li, Weiran; Liu, Shengfa; Yao, Zhengquan; Hu, Limin; Khokiattiwong, Somkiat; Kornkanitnan, Narumol
Highlights: Terrigenous sediment input in core ADM-9 was evidenced by the Sr–Nd isotopic results. Sensitive grain size can be used as an indicator of the ISM intensity. The evolution of the ISM was reconstructed via the records of grain size and element ratios. Abstract: Paleoenvironment and paleoclimate change in the Andaman Sea during the last 26 ka were reconstructed from high-resolution records of grain-size, major elements and Sr–Nd isotopes in core ADM-9. The values of ε Nd (0) and 87 Sr/ 86 Sr were in good agreement with those of Irrawaddy River sediments, indicating a common source of origin. Two sensitive grain-size intervals (3.4–7.5 and 16.8–21.2 μm) were identified; the former was controlled primarily by sea-level change, whereas the latter was related to Irrawaddy River discharge and South-west Current transport driven by the Indian Summer Monsoon (ISM). Proxies of chemical weathering (K/Al) and terrigenous input (Ti/Ca) coupled with sensitive grain-size interval (16.8–21.2 μm population) revealed that the ISM was weak during ∼15–26 ka BP and then strengthened gradually to a maximum during ∼7–9 ka BP; subsequently, the ISM exhibited a generally declining trend to ∼2 ka BP. The variation in the ISM recorded in this work is consistent with ISM variations observed in an open area in the northern Indian Ocean and adjacent continents, implying the evolution of the Asia Summer Monsoon since 26 ka.